Experience of stress and job satisfaction among government and private elementary school teachers - Kamil, Nur Kamalia Mohd; Olagoke, Salami Mutiu (University of Muhammadiyah Malang, 2023)
Changes in the teaching methods of students, especially during the COVID-19 crisis phase and the endemic transition, caused increased teacher stress. Therefore, this study examines the relationship between teacher stress and job satisfaction among government and private elementary school teachers. This study used a cross-sectional survey design in which elementary school teachers in Gombak were selected by convenience sampling. One hundred and fifty elementary school teachers participated in this study, including 75 government and 75 private elementary school teachers. The online questionnaire consists of the Teacher Stress Inventory (TSI) and the Short-Form Minnesota Questionnaire (MSQ). Descriptive analysis, Pearson’s correlation, and the independent t-test were used to find the relationship between teacher stress and job satisfaction and the difference between teacher stress and job satisfaction between government and private elementary school teachers. Findings revealed a negative correlation between teacher stress and job satisfaction [r(148)= -0.23, p = 0.005]. Furthermore, there is a significant difference in teacher stress and job satisfaction between government and private elementary school teachers [t(148) = 2.50, p = 0.014]. Private school teachers have been found to have higher teacher stress and job satisfaction than government school teachers. Although, with some limitations, the present study has contributed to existing knowledge and literature identifying why teachers’ well-being needs greater attention, as well as alarming the management of both private and government schools, providing avenues to reduce the stress level among teachers in promoting job satisfaction and enhancing teaching effectiveness.